Biotechnological Management of Angiopathic Wounds: Challenges and Perspectives. (December 2018) - Jiang, Yufeng; Li, Meirong; Fu, Xiaobing
Angiopathic wound is a wound that develops as a result of a local vascular lesion. Angiogenesis is an important aspect underlying repair, and increased angiogenesis could accelerate and improve the healing outcome. Biotherapy has been used more and more in clinic and brings hope for angiopathic wound treatment, through the rapid recovery of angiogenesis and regulation and correction of the whole wound microenvironment. In this article, we discuss the advantages and disadvantages of various technologies ranging from presentation of angiogenic growth factors, genetic strategies, stem cells, and biomaterials engineering in angiopathic wound treatment.